TASAWUF ‘IRFANI DAN IMPLEMENTASINYA DALAM PENDIDIKAN AGAMA ISLAM - Siti Mutholingah (Piwulang: Jurnal Pendidikan Agama Islam, 2020)
Sufism is a discipline that is not only related to efforts to improve individual morals in achieving ma'rifatullah, but actually Sufism is also closely related to efforts to improve the morals of others, especially in this context is through Islamic Religious Education (PAI). The teachings in Sufism of irfani are very urgent to be implemented in everyday life, including in this case is in the context of Islamic Religious Education. Why is that, this is because the main goal of PAI is to form humans capable of being Abdullah (pious individually) as well as khalifatullah (pious socially). To achieve both of these objectives, the existence of Sufism which culminates in achieving ma'rifatullah and mahabbatullah is very urgent if implemented in PAI. Maqamat or hierarchies in Tasawuf of ‘irfani can be a means for a PAI teacher to be able to achieve the goals of Islamic Religious Education.Tasawuf merupakan disiplin ilmu yang tidak hanya berkaitan dengan upaya memperbaiki akhlak individu saja dalam mencapai ma’rifatullah, tetapi sesungguhnya tasawuf juga erat kaitannya dengan upaya memperbaiki akhlak orang lain, khususnya dalam konteks ini adalah melalui Pendidikan Agama Islam (PAI). Ajaran dalam tasawuf irfani ini sangat urgen diimplementasikan dalam kehidupan sehari-hari, termasuk dalam hal ini adalah dalam konteks Pendidikan Agama Islam. Mengapa demikian, hal ini dikarenakan tujuan utama dari PAI adalah untuk membentuk manusia mampu menjadi abdullah (shaleh secara individu) sekaligus khalifatullah (shaleh secara sosial). Untuk mencapai kedua tujuan tersebut, maka keberadaan tasawuf irfani yang puncaknya adalah untuk mencapai ma’rifatullah dan mahabbatullah maka sangat urgen jika didimplementasikan dalam PAI. Maqamat-maqamat dalam tasawuf ‘irfani itu bisa menjadi sarana bagi seorang guru PAI untuk bisa menjadi mencapai tujuan Pendidikan Islam Agama itu sendiri.